Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/hiv.12073
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the interval between the initiation of antiretroviral therapy and the initiation of anti‐tuberculosis treatment in HIV/tuberculosis‐coinfected patients: results from the TREAT Asia HIV Observational Database

Abstract: Objectives We evaluated the effect of time intervals between the initiation of antiretroviral therapy (ART) and tuberculosis (TB) treatment on clinical outcomes in HIV-TB co-infected patients in an Asian regional cohort. Methods Adult HIV-TB co-infected patients in an observational HIV cohort database who had a known date of ART initiation and history of TB treatment were eligible for study inclusion. The time intervals between the initiation of ART and TB treatment were categorized as follows: TB diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 22 publications
(29 reference statements)
1
19
2
Order By: Relevance
“…The mortality rate in our study is considerably higher when compared to the mortality rates reported in previous studies from the same region, which ranged from 1.46/100pys to 3.77/100pys (1, 3). The large difference could be due to the short follow-up time, which is a limitation of our study.…”
Section: To the Editorcontrasting
confidence: 83%
See 2 more Smart Citations
“…The mortality rate in our study is considerably higher when compared to the mortality rates reported in previous studies from the same region, which ranged from 1.46/100pys to 3.77/100pys (1, 3). The large difference could be due to the short follow-up time, which is a limitation of our study.…”
Section: To the Editorcontrasting
confidence: 83%
“…To further expand on available data around TB co-infection and associated treatment outcomes in HIV-infected patients in Asia (1), we investigated survival outcomes in HIV-positive-TB co-infected patients.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies explicitly reported on how death was ascertained or confirmed (Table 2) [38], [39], [45].…”
Section: Resultsmentioning
confidence: 99%
“…A study investigating the risk of TB diagnosis after recruitment into the TREAT Asia HIV Observational Database (TAHOD) reported TB incidence of 1.98 per 100 person-years of follow-up with younger age, lower CD4 cell count, antiretroviral therapy (ART) duration, and living high TB burden countries being significantly associated with the diagnosis of TB (11). Additionally, it was found that delayed ART initiation after TB therapy did not affect mortality rates in TAHOD patients (12). …”
Section: Introductionmentioning
confidence: 99%